2016
DOI: 10.1123/jtpe.2015-0110
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Physical Fitness, and Health-Related Quality of Life in School-Aged Children

Abstract: Purpose:This study examined the association between physical activity (PA), physical fitness, and health-related quality of life (HRQOL) among school-aged children.Methods:Participants were 201 children (91 boys, 110 girls; Mage = 9.82) enrolled in one school in the southern US. Students’ PA (self-reported PA, pedometer-based PA) and physical fitness (cardiorespiratory fitness, muscular fitness, flexibility, and body composition) were assessed in the fall. The PedsQL4.0 (Varni et al., 2001) was used to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
85
2
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 40 publications
15
85
2
10
Order By: Relevance
“…cardiorespiratory fitness was positively associated with HrQOL, assessed using the PedsQL instrument, in physical and mental functioning dimensions [9]. Similar results were found in a sample of Portuguese adolescents.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…cardiorespiratory fitness was positively associated with HrQOL, assessed using the PedsQL instrument, in physical and mental functioning dimensions [9]. Similar results were found in a sample of Portuguese adolescents.…”
Section: Discussionsupporting
confidence: 73%
“…The results found for muscular strength are contrary to those described in young people from the United States and Spain [9,11]. Gu et al [9] demonstrated that muscular strength is associated with HrQOL in physical and mental functioning dimensions.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations